2020
DOI: 10.3390/cells9010194
|View full text |Cite
|
Sign up to set email alerts
|

Myxobacteria-Derived Outer Membrane Vesicles: Potential Applicability Against Intracellular Infections

Abstract: In 2019, it was estimated that 2.5 million people die from lower tract respiratory infections annually. One of the main causes of these infections is Staphylococcus aureus, a bacterium that can invade and survive within mammalian cells. S. aureus intracellular infections are difficult to treat because several classes of antibiotics are unable to permeate through the cell wall and reach the pathogen. This condition increases the need for new therapeutic avenues, able to deliver antibiotics efficiently. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Each isolate produces a variety of secondary metabolites, some of which have been exploited for drug development. [29][30][31][32] Myxobacterial OMVs are predatory in their own right, with purified OMVs able to inhibit growth and kill both Gram-negative and Gram-positive prey bacteria, [33][34][35] and several proteomics studies have investigated the composition of myxobacterial OMVs. [35][36][37][38] However, no studies have compared the proteomes of myxobacterial OMVs from different strains, or indeed characterised the OMV proteome for any strain beyond the model organism M. xanthus DK1622.…”
Section: Introductionmentioning
confidence: 99%
“…Each isolate produces a variety of secondary metabolites, some of which have been exploited for drug development. [29][30][31][32] Myxobacterial OMVs are predatory in their own right, with purified OMVs able to inhibit growth and kill both Gram-negative and Gram-positive prey bacteria, [33][34][35] and several proteomics studies have investigated the composition of myxobacterial OMVs. [35][36][37][38] However, no studies have compared the proteomes of myxobacterial OMVs from different strains, or indeed characterised the OMV proteome for any strain beyond the model organism M. xanthus DK1622.…”
Section: Introductionmentioning
confidence: 99%
“…Chemokines [25] Extracellular Vesicles and Gram-negative Beta-lactamase, coagulation factor, penicillin-binding protein [24,[37][38][39] Myxobacteria Chaperonin GroEL1, GroEL2, hydrolase, peptidase [24,40,41] Blood cells Platelets CD31, CD41, CD42a, CD62, C-type lectin, CXCR4, GPIIb/IIIa, PF4, SDF-1α [24,[42][43][44] Erythrocytes Glycophorin A, stomatin [24,34] Reticulocytes Galectin-5 [42,45] Bone cells Osteoblasts Cadherin-11 [42,46] Cancer cell lines Breast cancer cells (MM231, MM231LN)…”
Section: Phosphoproteinsmentioning
confidence: 99%
“…OMVs produced by two additional myxobacterial strains, SBSr073 and Cbv34, were also shown to inhibit E. coli growth, a property the authors attributed to the presence of cystobactamids (myxobacterial-derived inhibitors of bacterial gyrase) within the OMVs ( 68 ). This group subsequently showed that OMVs produced by CBv34 and Cbfe23 (another myxobacterial strain) were taken up by host cells and inhibited intracellular growth of Staphylococcus aureus cells ( 69 ).…”
Section: Natural Antibiotic Properties Of Omvsmentioning
confidence: 99%